2021
DOI: 10.31234/osf.io/2anrt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stop or Go? Playing Violent Games Reduces Inhibitory Control in Adolescents

Abstract: Despite growing body of research on video games effect on enhanced cognitive functioning, a relationship between violent video game exposure (VVGE) and inhibitory control is still poorly understood. Investigating inhibitory control mechanisms in relation to VVGE may help to better explain processes underlying aggression. This holds especially for adolescent players, who often play M-rated violent video games, and whose ability to inhibit responses is still developing. In two studies performed in adolescent sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
4

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 63 publications
(129 reference statements)
0
4
4
Order By: Relevance
“…While the results of Study 2 (Chapter 2) showed no effects of violent gaming on inhibitory control, the correlational Study 1 suggested that higher exposure to violent video games was related to better (and not worse) inhibitory control in adolescents. This result is not in line with our earlier research on inhibitory control among adolescents (Miedzobrodzka et al, 2021b), suggesting that both habitual VVGE and short-term exposure to violent gaming may be related to, and result in, respectively, weaker inhibitory control. Possible explanations of these inconclusive findings are: (1) use of different stimuli: neutral (arrows; Miedzobrodzka et al, 2021b) versus emotional faces (angry or disgusted;…”
Section: Theoretical Implications: Inhibitory Controlcontrasting
confidence: 99%
See 4 more Smart Citations
“…While the results of Study 2 (Chapter 2) showed no effects of violent gaming on inhibitory control, the correlational Study 1 suggested that higher exposure to violent video games was related to better (and not worse) inhibitory control in adolescents. This result is not in line with our earlier research on inhibitory control among adolescents (Miedzobrodzka et al, 2021b), suggesting that both habitual VVGE and short-term exposure to violent gaming may be related to, and result in, respectively, weaker inhibitory control. Possible explanations of these inconclusive findings are: (1) use of different stimuli: neutral (arrows; Miedzobrodzka et al, 2021b) versus emotional faces (angry or disgusted;…”
Section: Theoretical Implications: Inhibitory Controlcontrasting
confidence: 99%
“…This result is not in line with our earlier research on inhibitory control among adolescents (Miedzobrodzka et al, 2021b), suggesting that both habitual VVGE and short-term exposure to violent gaming may be related to, and result in, respectively, weaker inhibitory control. Possible explanations of these inconclusive findings are: (1) use of different stimuli: neutral (arrows; Miedzobrodzka et al, 2021b) versus emotional faces (angry or disgusted;…”
Section: Theoretical Implications: Inhibitory Controlcontrasting
confidence: 99%
See 3 more Smart Citations